Peace of mind for patients with differentiated thyroid cancer? - Vrachimis, A.; Riemann, B.; Gerss, J.; Maier, T.; Schober, O. (Nuklearmedizin - NuclearMedicine, 2013)
Differentiated thyroid carcinomas (DTC) have an excellent prognosis, with 10-year overall survival rates over 90%. In addition, DTC patients benefit from their lifelong medical surveillance. The aim of the study was to compare the patients’ overall survival with that of a matched general population. Patients and methods: We have analyzed 1497 consecutive patients with DTC, who underwent radioiodine therapy in Münster, Germany, according to international standards. We classified our patients according to the current 7th edition of the UICC (Union Internationale Contre le Cancer) classification and we compared the overall survival of the patients with the expected survival based on age and sex of the general population as provided by the Federal Statistical Office, Germany. Results: There were no significant differences in overall survival rates between DTC patients of the cohort in stages I to IVa compared to the expected survival based on age and sex of the general population. However, patients in stage IVc showed a significantly worse overall survival rate using the log-rank test (p < 0.0001). Conclusion: Patients with DTC showed excellent overall survival rates in stages I, II, III and IVa. All patients, except for those in stage IVc (M1 ≥ 45 years), had overall survival rates similar to the general population.
Keywords: Overall survival; expected survival; thyroid cancer